2016
DOI: 10.1002/acr.22775
|View full text |Cite
|
Sign up to set email alerts
|

Link Between Positive Clinician‐Conveyed Expectations of Treatment Effect and Pain Reduction in Knee Osteoarthritis, Mediated by Patient Self‐Efficacy

Abstract: Objective A prior knee osteoarthritis (OA) trial found that provider conveyed expectations for treatment success were associated with pain improvement. We hypothesized this relationship was mediated by patient self-efficacy since expectations of improvement may enhance one’s ability to control health behaviors, and therefore health. Our aim was to examine whether self-efficacy was a mediator of the relationship observed in this trial. Methods A secondary analysis of a three arm (traditional acupuncture, sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…Those findings, together with the fact that in previous studies have found effects of verbal suggestions, varied depending on the route of administration of the therapy, with larger effects in cases involving invasive treatments versus non-invasive treatments [ 43 , 44 ], which could partly explain why, in our study, no differences were observed between the different types of suggestions, since neither tapping, being a painful technique and on the other hand being an invasive therapy, could activate endogenous modulation systems. In contrast, other studies in patients with osteoarthritis who received verbal suggestions associated with acupuncture treatment, but applied to acupuncture points other than those necessary to produce an effect, produced a greater improvement in patients than the group who received a neutral suggestion [ 45 ] which was maintained for 3 months. Even a recent narrative review found that positive verbal suggestions have favorable effects on osteoarthritis pain and low back pain [ 46 ].…”
Section: Discussionmentioning
confidence: 85%
“…Those findings, together with the fact that in previous studies have found effects of verbal suggestions, varied depending on the route of administration of the therapy, with larger effects in cases involving invasive treatments versus non-invasive treatments [ 43 , 44 ], which could partly explain why, in our study, no differences were observed between the different types of suggestions, since neither tapping, being a painful technique and on the other hand being an invasive therapy, could activate endogenous modulation systems. In contrast, other studies in patients with osteoarthritis who received verbal suggestions associated with acupuncture treatment, but applied to acupuncture points other than those necessary to produce an effect, produced a greater improvement in patients than the group who received a neutral suggestion [ 45 ] which was maintained for 3 months. Even a recent narrative review found that positive verbal suggestions have favorable effects on osteoarthritis pain and low back pain [ 46 ].…”
Section: Discussionmentioning
confidence: 85%
“…The search strategy identified 22,402 studies, of which 164 full texts were screened to determine eligibility (Figure 2). Nine Three studies assessed the mediational role of self-efficacy (22,27,29), 2 studies assessed the mediational role of body weight (21,24), and single studies assessed the mediational role of knee muscle perfusion (25), knee extensor strength (26), the external knee adduction moment (28), inflammatory biomarkers (23), knee pain (27), physical activity (27), dietary intake (27) and pain beliefs (24). One study reported on the mediational effect of cardiovascular fitness on WOMAC summary score (21); however data specific to pain and physical function were not retrievable.…”
Section: Resultsmentioning
confidence: 99%
“…The current study extends understanding of the mechanisms through which contextual factors may impact patient health outcomes. Earlier studies have investigated pathways among smaller numbers of contextual variables and suggested, for example, that self-efficacy mediates the impact on osteoarthritis pain of practitioners communicating positive expectancies, 35 affective aspects of the therapeutic relationship may shape Open access patient expectancies in chronic pain, 70 and expectancies might impact pain via reduced catastrophising in chronic back pain. 33 The current results further suggest contextual factors reduce back-related disability in part by enhancing patient self-efficacy for coping with pain, reducing the perceived threat of pain and reducing psychosocial distress.…”
Section: Discussionmentioning
confidence: 99%
“…Such components include: positive and empathetic patient–practitioner relationships and a strong patient–practitioner alliance 4–10 (patient–practitioner relationship); patients’ outcome expectancies and perceived treatment credibility 9 11–16 (patient beliefs); musculoskeletal practitioners’ beliefs about pain 17–22 and outcome expectancies 23 (practitioner beliefs); good organisational environments (eg, collegiality) 24 , the physical–sensory environment (eg, music) 25 and the healthcare sector 26–28 (environment), although evidence of effects of healthcare sector on patient outcomes is mainly qualitative. Contextual components might impact patient outcomes via (1) behavioural pathways (eg, improved self-management), 29 30 but see also Haanstra et al who found that adherence accounted for only a small proportion of the relationship between expectancies and pain outcomes, 31 (2) psychosocial pathways (eg, reconceptualising pain as less threatening 32–34 ; increased self-efficacy 35 36 ) and/or (3) neurophysiological pathways. 37–41 The focus in this study was on psychosocial pathways; more details on how these were hypothesised to operate are provided in our published protocol.…”
Section: Introductionmentioning
confidence: 99%